Development of a capillary electrophoresis method with direct UV detection for the analysis of thiodiglycol and its oxidation products. Issue 9 (22nd April 2015) - Jõul, Piia; Lees, Heidi; Vaher, Merike; Kobrin, Eeva‐Gerda; Kaljurand, Mihkel; Kuhtinskaja, Maria
Abstract : A novel method based on CE with precolumn derivatization and direct UV detection for the determination of thiodiglycol (TDG), TDG sulfoxide, and TDG sulfone in water samples was developed. The lack of a UV chromophore of target analytes was overcome by derivatization with phthalic anhydride. The reactant concentrations, as well as the derivatization dependence on heating temperature and time, were carefully investigated. The baseline separation of three derivatives was achieved in less than 8 min by applying a simple BGE composed of a 30 mM borate buffer at pH 8.5. Several parameters affecting the separation efficiency (buffer pH and concentration, capillary temperature, and applied voltage) were evaluated. Calibration curves of all compounds showed good linear correlations ( R 2 > 0.9994). The LODs of the TDG and its oxidation products were in the range of 98–154 ng/mL. The precision tests resulted in RSDs for migration times and peak areas of less than 1.2 and 3.6%, respectively. The developed method was successfully applied for the analysis of TDG and oxidation products in seawater, utilizing the carbon aerogel‐based adsorbents for sample purification and concentration. Additionally, the method has the potential to be transformed into a portable CE format.